Assessment of nursing workload in adult psychiatric inpatient units: A scoping review. Issue 7 (8th June 2018) - Sousa, Carla; Seabra, Paulo
Accessible summary: What is known on the subject?: There is a shortage of empirical research in the field of psychiatric and mental health nursing regarding how to calculate a safe staffing level in psychiatry inpatient units. Furthermore, the tools to assess nursing workload in this specialty are limited. No systematic reviews on measurement tools in adult psychiatric inpatient settings were found. What does this paper add to existing knowledge?: This study confirms the scarcity and heterogeneity of instruments with which to evaluate nursing workload in this specific context. Likewise, the instruments identified do not capture the complexity of the psychiatric nursing setting, namely, the relational and psychotherapeutic strategies that must be implemented in the patient care approach. The findings of the study suggest that evidence‐based tools for adult psychiatric inpatient settings require further development. What are the implications for practice?: This review shows the need to continue to develop tools that assess workload in psychiatric inpatient units that embrace activities related to patient (direct and indirect) and nonpatient activities. The great challenge is providing a sensitive understanding of the workload resulting from psychotherapeutic interventions, the primary treatment that many patients need. This review reinforces the need to add patient outcomes to workload assessment processes. Abstract: Introduction: No systematic reviews on measurement tools in adult psychiatric inpatient settings exist in the literature, and thus, further research is required on ways to identify approaches to calculate safe nurse staffing levels based on patients' care needs in adult psychiatric inpatient units. Aim: To identify instruments that enable an assessment of nursing workload in psychiatric settings. Method: A scoping review was conducted. Results: Four studies were identified, with five instruments used to support the calculation of staff needs and workload. All four studies present methodological limitations. Two instruments have already been adapted to this specific context, but validation studies are lacking. Discussion: The findings indicate that the tools used to evaluate nursing workload in these settings require further development, with the concomitant need for more research to clarify the definition of nursing workload as well as to identify factors with the greatest impact on nursing workload. Implications for practice: This review highlights the need to develop tools to assess workload in psychiatric inpatient units that embrace patient‐related and non‐patient‐related activities. The great challenge is to enable a sensitive perception of workload resulting from nurses' psychotherapeutic interventions, an important component of treatment for many patients.